2014
DOI: 10.1097/acm.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Applying Athletic Principles to Medical Rounds to Improve Teaching and Patient Care

Abstract: The new rounding system has the potential to reduce waste and improve the quality of patient care while improving caregiver satisfaction and medical student teaching. Adaptive leadership skills will be required to overcome resistance to change. The use of athletic analogies can improve teamwork and facilitate the adoption of a systems approach to the delivery of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 1 publication
0
47
0
Order By: Relevance
“…25,30 Questions assessed satisfaction with AR, perceived value of bedside rounds, and extent of patient and nursing involvement. Level of agreement with each item was captured on a continuous scale; 0 = strongly disagree to 100 = strongly agree, or from 0 (far too little) to 100 (far too much), with 50 equating to "about right."…”
Section: Healthcare Provider Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…25,30 Questions assessed satisfaction with AR, perceived value of bedside rounds, and extent of patient and nursing involvement. Level of agreement with each item was captured on a continuous scale; 0 = strongly disagree to 100 = strongly agree, or from 0 (far too little) to 100 (far too much), with 50 equating to "about right."…”
Section: Healthcare Provider Outcomesmentioning
confidence: 99%
“…One involved the implementation of interprofessional patient-centered bedside rounds on a nonteaching service, 24 while the other evaluated the impact of integrating athletic principles into multidisciplinary work rounds. 25 Work at our institution had sought to develop AR practice recommendations to foster an optimal patient experience, while maintaining provider workflow efficiency, facilitating interdisciplinary communication, and advancing trainee education. 26 Using these AR recommendations, we conducted a prospective randomized controlled trial to eval- uate the impact of implementing a standardized bedside AR model on patient satisfaction with rounds.…”
mentioning
confidence: 99%
“…Southwick et al 51 found that BR as part of a bundled intervention led to a statistically significant reduction in 30-day readmission (6.95% vs 9.95%, p=0.039) and relative LOS (0.76 vs 0.93, p=0.01). Another bundled BR intervention was also associated with a reduction in LOS (4.5 days vs 5.0 days, p=0.001) 28.…”
Section: Resultsmentioning
confidence: 99%
“…Implicit in medical education, but not often didactically taught, is the ability to successfully work in teams for the collective aim of improving and streamlining patient care and quality of life. More recently, directed interventions at improving medical teamwork have been systematically studied [4,5]. The use of teamwork skills borrowed from athletic teams on medical rounds was demonstrated to decrease 30-day readmission rates and improve caregiver satisfaction and medical student teaching [5].…”
Section: Teamwork Leadership and Medicinementioning
confidence: 99%
“…More recently, directed interventions at improving medical teamwork have been systematically studied [4,5]. The use of teamwork skills borrowed from athletic teams on medical rounds was demonstrated to decrease 30-day readmission rates and improve caregiver satisfaction and medical student teaching [5]. In a breast oncology center, team training (via a train-the-trainer method) improved communication, task coordination, and perceptions of efficiency, quality, safety, and interactions among team members along with patient perception of care coordination.…”
Section: Teamwork Leadership and Medicinementioning
confidence: 99%